Abruptio placenta retrospective study: maternal and fetal outcome - Sambath, Shanthadevi; V. H., Vanitha Rukmani; S., Subalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Placental abruption is the most common cause of antepartum haemorrhage. Incidence appears to be increasing due to increase in prevalence of risk factors like age, parity, anaemia, poor nutrition, Preeclampsia, PROM, previous MTP. Abruption may be partial or total. Pain and Vaginal bleeding hallmark of abruption. Methods: Retrospective observational study carried out during period of October 2017 to October 2018 at Govt Theni medical college- tertiary care institute. To investigate incidence, cause, maternal and perinatal outcome. Maternal Data includes incidence, age, parity, gestational age, risk factors, intra-operative events, amount of blood loss. Other causes of APH-Placenta praevia and extra-placental causes are excluded. Neonatal data includes Term/preterm, Birth weight, NICU admission, perinatal morbidity and mortality. Results: Total number of deliveries from October 2017 to September 2018 were 7010. Total number of abruptio placenta cases were 55. This study shows increased incidence of severe preeclampsia with abruption. Increasing age as predisposing factor. Mean age of abruption was 26-30 years mainly seen in term pregnancy. Mode of delivery varied. Major complication were PPH and shock managed with blood products. Conclusions: This study reveals increasing age, parity, severe preeclampsia are risk factors. Routine and regular antenatal checkup early detection and correction of Preeclampsia, anemia helps to deduce no of abruption and improving maternal and fetal outcome though maternal morbidity is reduced with modern management of abruption, Timely diagnosis and intervention is necessary. Team efforts by obstetricians, anesthetist and neonatologist is required for better maternal and fetal outcome.